Raman spectroscopy in halophile research - Jehlicka, Jan; Oren, Aharon (Frontiers in Microbiology, 2013)
Raman spectroscopy plays a major role in robust detection of biomolecules and mineral signatures in halophile research. An overview of Raman spectroscopic investigations in halophile research of the last decade is given here to show advantages of the approach, progress made as well as limits of the technique. Raman spectroscopy is an excellent tool to monitor and identify microbial pigments and other biomolecules in extant and extinct halophile biomass. Studies of bottom gypsum crusts from salterns, native evaporitic sediments, halite inclusions and endoliths as well as halophile cultures permitted to understand the content, distribution and behavior of important molecular species. The first papers describing Raman spectroscopic detection of microbiological and geochemical key markers using portable instruments are highlighted as well.